ANTIDIABETIC ACTIVITY OF ETHANOLIC EXTRACT OF KALANCHOE PINNATA LEAVES IN ALLOXAN INDUCED HYPERGLYCAEMIC RATS. - Indah DD (Indonesian Journal of Pharmacy, 2016)
Diabetes remains a major burden in health care both in developed and developing countries. Kalanchoe pinnata has been used as a traditional medicine to treat diabetes. We try to find scientific evidence of antidiabetic activity of Kalanchoe pinnata extract (KPE) through hypoglycemic effect using animal model of diabetes mellitus. Hyperglycaemia was developed in rats using alloxan 150 mg/kgBW. Three days after alloxan injection, rats having fasting blood glucose (FBG) >200 mg/dL were divided into six groups, namely HG (hyperglycaemia), HG+KPE high-dose (hyperglycaemia+KPE 33.2 mg/kg), HG+ KPE medium-dose (hyperglycaemia+KPE 11.6 mg/kg), HG+KPE low-dose (hyperglycaemia+ KPE 5.8 mg/kg), standard drug 1 (hyperglycaemia+glibenclamidee 1.35 mg/kg), standard drug 2 (hyperglycaemia+acarbose 13.5 mg/kg). Then, FBG was measured every 5 days recorded as t1, t2, and t3 to determine fluctuations in blood glucose. At the end of the study, rats were sacrified, pancreas was collected and number of pancreatic beta cell langerhans was determined. KPE 11.6 mg/kg showed best hypoglycemic effect and improvement of the number of pancreatic beta cell langerhans. KPE has hypoglycemic effect through improvement of the number of pancreatic beta cell langerhans but not in dose dependent manner.